School Leadership and Inclusive Education Policy Implementation in Jamaican Primary Schools: Exploring Knowledge, Challenges, and Opportunities - Anderson Leachman, Kishi (Exceptionality Education International)

(untitled) (University of Western Ontario, 2026)
This study explores the perspectives and experiences of school principals and ministry leaders regarding the implementation of inclusive education policy in Jamaican public primary schools. Using a qualitative multiple-case-study approach, six participants—four principals and two ministry leaders—were interviewed to understand their knowledge of inclusive policies and the challenges principals and ministry leaders faced in practice. Despite Jamaica’s policy commitments to inclusive education, findings revealed gaps in knowledge, resources, and support that impacted effective implementation. School leaders highlighted both successes and obstacles in fostering inclusive environments, emphasizing the need for increased professional development, collaborative leadership, and systemic support. This study contributes to the limited literature on inclusive education leadership in the Caribbean context and offers practical insights for policymakers aiming to strengthen inclusive practices in Jamaican schools.